I hope you are trying to write
![i^0*i^1*i^2*i^3*i^4](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9uwmxj1hz01d87u77wxtf5fhk1rjjtkxxv.png)
Now,
Because any number to exponent 0 always result 1.
Any number to exponent 1 will result the same number.
By using the property of imaginary number.
![i^3= i^2*i =(-1)*i= -i](https://img.qammunity.org/2019/formulas/mathematics/middle-school/j9ve1kqwt2opqxubtca05tdf1vbe1m2kkv.png)
![i^4=i^2*i^2=(-1)*(-1)=1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/sxclcjplbbkrc3pa11djijsspyns7lrq0y.png)
Now we can plug in these values in the given expression to get the value of the expression. So,
![i^0*i^1*i^2*i^3*i^4](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9uwmxj1hz01d87u77wxtf5fhk1rjjtkxxv.png)
=
![1*i*(-1)*(-i)*1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/46f59x13l484iovqsr9uatd7193arn15wv.png)
=
![i^2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/lo4gxq2mp90hczgc4ns6chudev29zvrssh.png)
=-1
So, -1 is the correct choice.